Efektivitas Google Classroom dalam Pembelajaran Lesen Und Schreiben di Masa Pandemi Covid-19 - Nurming Saleh; Hasmawati Hasmawati; Misnah Mannahali; Nursalam Nursalam (Seminar Nasional LP2M UNM, 2021)
Abstrak. The study's purpose is to know the effectiveness of google classroom in learning Lesen und Schreiben courses during the COVID-19 pandemic for students of the German education department of the Faculty of Language and Literature Makassar State University. The research design of this study is quasi-experiment. The research was managed at the Faculty of Language and Literature by adopting online learning when giving treatment. A study sample of 25 students of the 2020/2021 academic year. Data on the study was obtained through reading and writing tests and documentation. This research data was analyzed by using the t-one tile test. The results of the analysis showed that Google classroom had significance to the competence of reading and writing German students with tscore (10,975) > ttable (1,714) in reading competence and tscore (8,292) > ttable (1,714) on writing competence. Based on the research data analysis, it can be concluded that google classroom is effective in learning Lesen und Schreiben for students of the German Language Education Study Program of the Faculty of Language and Literature UNM during the COVID-19 Pandemic. Kata Kunci: Google Classroom, Learning Lesen und Schreiben, the COVID-19 Pandemic